2007
DOI: 10.1074/jbc.m702112200
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid-inducible Gene-I and Interferon-β Promoter Stimulator-1 Augment Proapoptotic Responses Following Mammalian Reovirus Infection via Interferon Regulatory Factor-3

Abstract: During viral infection, cells initiate antiviral responses to contain replication and inhibit virus spread. One protective mechanism involves activation of transcription factors interferon regulatory factor-3 (IRF-3) and NF-B, resulting in secretion of the antiviral cytokine, interferon-␤. Another is induction of apoptosis, killing the host cell before virus disseminates. Mammalian reovirus induces both interferon-␤ and apoptosis, raising the possibility that both pathways are initiated by a common cellular se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
132
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(138 citation statements)
references
References 63 publications
5
132
0
Order By: Relevance
“…Expression profiling analysis of RNA isolated from U266 cells revealed that reovirus treatment induced a strong anti-viral response, which was characterized by interferon (IFN) stimulation (Supplementary Tables 1 and 2). Consistent with prior reports, reovirus exposure induces an IFN-b response (Hamamdzic et al, 2001;Holm et al, 2007;Steele et al, 2011). While IFN production has been reported to decrease viral spread and efficacy, IFNs have also been shown to elicit anti-tumor effects via inhibition of angiogenesis and stimulation of apoptosis (Sidky and Borden, 1987;Taylor et al, 2008;Shmulevitz et al, 2010).…”
Section: Resultssupporting
confidence: 81%
“…Expression profiling analysis of RNA isolated from U266 cells revealed that reovirus treatment induced a strong anti-viral response, which was characterized by interferon (IFN) stimulation (Supplementary Tables 1 and 2). Consistent with prior reports, reovirus exposure induces an IFN-b response (Hamamdzic et al, 2001;Holm et al, 2007;Steele et al, 2011). While IFN production has been reported to decrease viral spread and efficacy, IFNs have also been shown to elicit anti-tumor effects via inhibition of angiogenesis and stimulation of apoptosis (Sidky and Borden, 1987;Taylor et al, 2008;Shmulevitz et al, 2010).…”
Section: Resultssupporting
confidence: 81%
“…These findings taken together suggest that IPS-1 and PKR may cooperatively function in the cellular responses to virus infection. Our observations obtained with the ⌬E3L mutant VV are consistent with recent findings showing both IPS-1 and IRF-3 are required for efficient apoptosis induced by infection with reovirus Dearing-type 3 (T3D), a dsRNA virus (61). In Sendai virus-infected cells, the apoptotic response is impaired by siRNA knockdown of IRF-3 or by blocking the IRF-3 activation pathway via RIG-I (62).…”
Section: Discussionsupporting
confidence: 81%
“…These results are in line with a recent report showing a dominant proinflammatory response through TLR3 and a comparable proinflammatory and antiviral response through RIG-I after influenza A virus infection in human bronchial epithelial cells (49). Moreover, programmed cell death induction in mammalian reovirus-infected cells also seems to depend on a functional RIG-I-IRF3 axis, while RIG-I seems to be dispensable for NF-B-induced apoptosis (54). A possible explanation for this finding of increased IRF3 activity after endosomal inhibition of TLR3 can be derived from the results of Sato and colleagues, who have characterized the binding domain for TRAF6 with TRIF (57).…”
Section: Discussionsupporting
confidence: 81%